Impact of storage time and temperature on furanic derivatives formation in wines using microextraction by packed sorbent tandem with ultrahigh pressure liquid chromatography - Perestrelo, Rosa (2019)
his paper reports the effect of storage temperature, storage time and glucose content on furanic derivatives (FDs) formation in fortified Madeira wines using headspace solid phase microextraction (HS–SPME) combined with gas chromatography-quadrupole mass spectrometry (GC–qMS), and microextraction by packed sorbent (MEPS) tandem with ultrahigh pressure liquid chromatography coupled to photodiode array detection (UPLC–PDA). Based on the results obtained, MEPS/UPLC–PDA showed better FDs extraction compared to HS–SPME/GC–qMS, in terms of analysis reduction, sensitivity, reproducibility and allow detect all target furanic derivatives considered in this study. 5-Hydroxymethyl-2-furfural, one of the most abundant FDs in wines, is not detected by HS–SPME/GC–qMS, which suggest that this methodology is not the most suitable to achieve the purpose of this study. Regarding the impact of storage time and temperature on FDs formation using MEPS/UPLC–PDA, it was verified an increase on FDs concentration during storage time independently of storage temperature as well as glucose content, and this increase is also favored by temperature increases, being more significant at 55 °C. The results obtained in this study could be used as a useful tool in winemaking field in order to introduce changes in fermentation as well as baking (estufagem) process, and/or predict the effects of storage time by application of high temperatures.